2001
DOI: 10.1111/j.1349-7006.2001.tb01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Prevents Breast Cancer?

Abstract: To investigate the chemopreventive effects of seaweed on breast cancer, we have been studying the relationship between iodine and breast cancer. We found earlier that the seaweed, wakame, showed a suppressive effect on the proliferation of DMBA (dimethylbenz(a)anthracene)-induced rat mammary tumors, possibly via apoptosis induction. In the present study, powdered mekabu was placed in distilled water, and left to stand for 24 h at 4°C. The filtered supernatant was used as mekabu solution. It showed an extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 15 publications
3
84
0
5
Order By: Relevance
“…Furthermore, there are several reports regarding the preventive effect of seaweed consumption against breast cancer (Teas, 1983;Kang et al, 2004). However, it is important to recognize that to increase seaweed intake beyond current levels in Japan does not necessarily mean enhanced health benefits; indeed some researchers have shown disadvantages, for example, stimulatory effects upon cancers (Ashi et al, 1978;Watanabe et al, 1978;Reddy et al, 1985;Funahashi et al, 2001). Fiber intake pattern S Fukuda et al…”
Section: Fiber Intake Pattern S Fukuda Et Almentioning
confidence: 99%
“…Furthermore, there are several reports regarding the preventive effect of seaweed consumption against breast cancer (Teas, 1983;Kang et al, 2004). However, it is important to recognize that to increase seaweed intake beyond current levels in Japan does not necessarily mean enhanced health benefits; indeed some researchers have shown disadvantages, for example, stimulatory effects upon cancers (Ashi et al, 1978;Watanabe et al, 1978;Reddy et al, 1985;Funahashi et al, 2001). Fiber intake pattern S Fukuda et al…”
Section: Fiber Intake Pattern S Fukuda Et Almentioning
confidence: 99%
“…The putative protective effect of seaweed on breast cancer is in accord with the relatively low breast cancer rates in Japan (19) , where seaweed-rich diets are consumed and with the increasing breast cancer rates in Japanese women who emigrate (20) or consume a Western style diet (21) . Animal studies (10,22,23) and in vitro studies (23 -25) demonstrated the anticarcinogenic effects of seaweeds against mammary carcinogenesis. Iodine as well as other components of seaweeds have been suggested to act as antioxidants (26) and induce apoptosis in human breast cancer cell lines (23) .…”
mentioning
confidence: 99%
“…Animal studies (10,22,23) and in vitro studies (23 -25) demonstrated the anticarcinogenic effects of seaweeds against mammary carcinogenesis. Iodine as well as other components of seaweeds have been suggested to act as antioxidants (26) and induce apoptosis in human breast cancer cell lines (23) . In an ecological study, the regions where iodine intake was low had higher breast cancer mortality rates (27) .…”
mentioning
confidence: 99%
“…Funahashi et al reported recently that both Japanese edible Wakame seaweed and also a direct uptake of inorganic iodine [26] by tumor have experimentally a suppressive effect on DMBA-induced breast tumors growth in the rat. NIS expression is inversely related to undifferentiation, malignity and it is directly related to likelihood of therapeutic effectiveness of radioiodine therapy.…”
Section: Iodine and Thyroid Hormone In The Therapy Of Breast Diseasesmentioning
confidence: 99%